2009
DOI: 10.1002/jssc.200900165
|View full text |Cite
|
Sign up to set email alerts
|

Potential of adsorption isotherm measurements for closer elucidating of binding in chiral liquid chromatographic phase systems

Abstract: The human body is a chiral environment and many drugs are chiral and interact differently depending on the type of enantiomer. Therefore, the interest in analytical and preparative separations of enantiomers has steadily increased over the years. LC is today the most important technique in analytical laboratories worldwide. The key to understand the separation system lies in the adsorption isotherm, which describes the equilibrium distribution of solutes between the mobile and stationary phases. By measuring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 75 publications
(90 reference statements)
1
43
0
Order By: Relevance
“…Later, a numerical investigation ascertained the most favorable band-shape composition in preparative chromatography for a particular enantiomer [70]. These previous studies demonstrated adsorbing additives, in particular strongly bound, can have extreme impact on retention times and peak shapes [71,72]. We have previously prepared and evaluated two novel oligoproline CSPs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Later, a numerical investigation ascertained the most favorable band-shape composition in preparative chromatography for a particular enantiomer [70]. These previous studies demonstrated adsorbing additives, in particular strongly bound, can have extreme impact on retention times and peak shapes [71,72]. We have previously prepared and evaluated two novel oligoproline CSPs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To transfer dynamic LC adsorption isotherm acquisition methods [4,5,37] to SFC one must ensure that the column is operated at constant volumetric flow rate under isopycnic and isothermal conditions. Furthermore, it is also necessary to have accurate measurements of the actual mass flow, pressure and temperature in order for SFC experiments to be reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…To accurately determine adsorption isotherms using dynamic methods, as we do in this study, it is important to know the volumetric flow of the mobile phase in the column [4,5,9,37]. To calculate the volumetric flow, see Eq.…”
Section: Mass Flow Temperature and Pressurementioning
confidence: 99%
“…The outcome of a chromatographic separation is strongly dependent on the adsorption isotherms of the solutes, since they dictate the separation factors and saturation capacities, i.e., how much solute can be adsorbed. Therefore, estimation of adsorption isotherms is crucial and also gives deeper understanding of the separation processes [3,4,9,12,14,31].…”
Section: Introductionmentioning
confidence: 99%